Event Study of State-Owned Bank Stock Prices Before and After the Announcement of Danantara on February 24, 2025 - Zaenudin, Windi; Syarief, Mochamad Edman (Indonesian Journal of Economics and Management, 2025)
This research seeks to examine the variations in stock prices movements and trading activity of state-owned banks (BMRI, BBRI, BBNI, and BBTN) surrounding the announcement of the establishment of the Sovereign Wealth Fund "Badan Pengelola Investasi Daya Anagata Nusantara (Danantara)" on February 24, 2025. The research employs a quantitative method with an event study approach, using a 61-day observation period (30 days before and 30 days after the event). The indicators analyzed include Daily Stock Prices (HS), Average Abnormal Return (AAR), and Average Trading Volume Activity (ATVA). The results show a significant difference in HS, reflecting a decline in stock prices after the announcement, as a response to negative market sentiment. However, no significant difference was found in AAR, indicating the absence of abnormal market return reactions to the event. Meanwhile, a significant difference in ATVA was observed, indicating heightened stock trading volume in response to the announcement event. These findings provide insights for investors, regulators, and academics in understanding capital market responses to government strategic policies, highlighting the importance of transparency and effective communication in economic policymaking..